Liquidity sensitivity on stock returns : evidence from Malaysia companies listed in Bursa Malaysia / Jennifer Jepinus - Jepinus, Jennifer (2016)
Lam and Tarn (2011) stated that investors believe liquidity to be an essential factor when making the investment decisions. However, some researcher said that liquidity has not affecting the investor's returns. It is very important for the investor to know this matter since it can influence the investor's decision in making investment. The purpose of this study is to examine the relationship between the trading volume as the proxy for liquidity with the stock returns which has been a debate issue among the researchers. The general finding suggests that the liquidity which is trading volume give high return to the investor or not. This study used 39 companies that were selected from Bursa Malaysia using the convenience sampling technique between the period 2010-2014 and use the cross sectional analyses. In conclusion, there is insignificant relationship between trading volume and the stock return which it does not influence the investor's stock return.